(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The research looks at bases with pile foundations, bases reinforced by vertical reinforcing elements, and bases made from compacted soil pads. The research presents the findings of the modeling of vertical armo-elements on loess subsiding soils and foundation pads. The authors propose techniques for computing the fundamental parameters of bearing armo-element capacity and foundation pad. The study also includes the outcomes of actual base and foundation construction using this technique in Uzbekistan’s soil conditions.